2008
DOI: 10.1007/s00404-008-0680-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ramadan fasting on maternal serum lipids, cortisol levels and fetal development

Abstract: The results of this study showed that maternal serum cortisol level was elevated while LDL/HDL ratio were decreased in healthy women with uncomplicated pregnancies of 20 weeks or more, who were fasting during Ramadan. No untoward effect of Ramadan was observed on intrauterine fetal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 13 publications
4
67
1
Order By: Relevance
“…A significant fall in glucose, insulin, lactate and carnitine and a rise in triglycerides and hydroxybutyrate was reported at the end of the fasting day in pregnant women [116] . In another reports the LDL/HDL ratio was decreased and the outcome of pregnancy was comparable to those who did not fast [117,118] . The outcome of pregnancy in Gambian women who fasted during Ramadan was unsatisfactory; however, no control group was evaluated [119] .…”
Section: Pregnancy and Lactationmentioning
confidence: 98%
“…A significant fall in glucose, insulin, lactate and carnitine and a rise in triglycerides and hydroxybutyrate was reported at the end of the fasting day in pregnant women [116] . In another reports the LDL/HDL ratio was decreased and the outcome of pregnancy was comparable to those who did not fast [117,118] . The outcome of pregnancy in Gambian women who fasted during Ramadan was unsatisfactory; however, no control group was evaluated [119] .…”
Section: Pregnancy and Lactationmentioning
confidence: 98%
“…In fact, evidence from some countries indicates that 70-90% of pregnant women observe the fast [72], although surveys suggest that they may not manage the full month [70,73,74]. Some studies in healthy pregnant women, without diabetes, have shown no harmful effects of fasting on baby or mother [73,[75][76][77], although other studies have reported some negative outcomes [72,78,79].…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Although these changes in the maternal serum lipid profile are thought to be normal adaptations to support fetal development, studies have shown that some factors such as being overweight [1], sedentary behavior [3], smoking [4], vitamin B1 (thiamine) and B2 (riboflavin) deficiency [5] and lifestyle [6] negatively influence this increase.…”
Section: Introductionmentioning
confidence: 99%